Giorgio Vasari, Francisco Pacheco et le Jugement dernier - Anne-Sophie Molinié (Mélanges de la Casa de Velázquez, 2011)
This article takes a particular viewpoint (the subject of the Last Judgement), to discuss the possible importance of the writings of Giorgio Vassari for the Spanish theoretician Francisco Pacheco. For various reasons the two authors devoted numerous pages to this subject, and each illustrated it in a painting. Vassari’s, which was commissioned by the Pope, can still be viewed at Bosco Marengo in Piedmont; Pacheco’s was painted for the convent of Santa Isabel in Seville. A certain number of writings and engravings that were circulating in Spain in the late 16th and early 17th centuries have been collected together to demonstrate the dissemination of Italian or Nordic iconographic models and analyse the point of view that Pacheco impressed on his own interpretation of the subject as a theoretician and censor of the Inquisition. In short, the article seeks to evaluate the extent to which Giorgio Vassari’s writings influenced Francisco Pacheco’s thought, and more generally the reception of the Tuscan biographer’s writings and positions in the Iberian Peninsula.